2019
DOI: 10.4236/ojepi.2019.94023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV among Adolescent Children in Abuja, the Federal Capital Territory, Abuja Nigeria

Abstract: Adolescents in Africa have low HIV testing rates. Determining the HIV prevalence among this group is very important because adolescents living with HIV (ALHIV) have worse health outcome than other populations of people living with HIV. This study aimed at determining the prevalence of HIV among children of adolescents age (10-18 years) that come for HIV testing in virology laboratory of National Institute for Pharmaceutical Research and Development, Abuja from January 2013 to December 2018. The result was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
2
2
Order By: Relevance
“…The study revealed that more female sex workers are infected with HIV than the male counterparts. This is in comparison to the findings of [24] of 2.74% among FSW and 2.67% among MSW, 6.24% among females and 1.58% among males by [22]. The study indicated that 1.58% prevalence of HIV among MSW is lower than the findings of 5.3% from China [25] and 6.25 by [22], but comparable to 1.4% among MSWs in Northern Mexico [23].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…The study revealed that more female sex workers are infected with HIV than the male counterparts. This is in comparison to the findings of [24] of 2.74% among FSW and 2.67% among MSW, 6.24% among females and 1.58% among males by [22]. The study indicated that 1.58% prevalence of HIV among MSW is lower than the findings of 5.3% from China [25] and 6.25 by [22], but comparable to 1.4% among MSWs in Northern Mexico [23].…”
Section: Discussioncontrasting
confidence: 53%
“…This is in comparison to the findings of [24] of 2.74% among FSW and 2.67% among MSW, 6.24% among females and 1.58% among males by [22]. The study indicated that 1.58% prevalence of HIV among MSW is lower than the findings of 5.3% from China [25] and 6.25 by [22], but comparable to 1.4% among MSWs in Northern Mexico [23]. HIV prevalence in FSW varies within and across west African countries, the findings of this study showed a lower prevalence compare to 20% by [26] 24.75% by [22].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations